Celebration Drinking around the Clock. Issue 11 (18th September 2020) - Smith, Sandi W.; Alhabash, Saleem; Kanver, Duygu; Tan, Pang-Ning; Viken, Greg
ABSTRACT: The fact that St. Patrick's Day (SPD) celebration drinking occurs during a specified, public, and socially-acceptable time frame which spans the better part of a day and evening makes it an important time to understand and attempt to influence celebration drinking behaviors among young adults. SPD has been identified as the celebration during which college students consume more alcohol than any other point during the school year. Intervention opportunities can be more successful with an understanding of the factors associated with alcohol consumption at specific times on particular celebrations. This study examined the factors associated with celebration drinking at different time periods on SPD which included perceived descriptive and injunctive norms, the numbers of close friends and acquaintances present, social media relationships, demographic variables, past drinking behavior, and intent to drink on SPD at the three time points of interest. Findings showed variability in the predictive factors on SPD celebration drinking at different times of the day. The theoretical and practical intervention implications of the findings are discussed.